Intracranial Germ Cell Tumors - Yeoh, Teri Danielle You Ying; Nga, Vincent; Kimpo, Miriam; Lo, Simon S.; Vellayappan, Balamurugan (Seminars in Neurology, 2023)
Intracranial germ cell tumors are rare tumors occurring in adolescents and young adults, which include germinomas and non-germinomatous type germ cell tumors (NGGCT). In the past few decades, cooperative trial groups in Europe and North America have developed successful strategies to improve survival outcomes and decrease treatment-related toxicities. New approaches to establishing diagnosis have deferred the need for radical surgery. The 5-year event-free survival (EFS) is above 90% and even patients who present with metastatic germinoma can still be cured with chemotherapy and craniospinal irradiation. The combination of surgery, chemotherapy, and radiation therapy is tailored to patients based on grouping and staging. For NGGCT, neoadjuvant chemotherapy followed by delayed surgery for residual disease and radiotherapy can yield a 5-year EFS of 70%. Further strategies should focus on reducing long-term complications while preserving high cure rates.
Keywords: intracranial germ cell tumor; germinoma; non-germinomatous germ cell tumor; whole ventricular radiotherapy